Strategi Komunikasi Politik Partai Baru (Studi Kasus Perolehan Suara Partai Solidaritas Indonesia di DPRD DKI Jakarta Pada Pemilu 2019) - Bella Adha Hendriana Moneter; Eko Harry Susanto (Koneksi, 2020)
The 2019 legislative elections participated by many political parties in Indonesia, one of which was the Indonesian Solidarity Party (PSI). The more parties that participate in the General Election, the competition between each one of them become more strict in order to get a seat in parliament. Due to that reason, PSI did not pass on the DPR RI election level but somehow managed to get a 6.68% vote and get eight seats on the Jakarta DPRD election level. In this case, the purpose of this research is to study the political communication strategy of PSI Jakarta regarding the vote they got on Jakarta DPRD election level in 2019 General Election. This research is using the conceptualization of political policy, the conceptualization of political communication strategy, conceptualization of political policy, and conceptualization of political policy. political policy, and conceptualization of general elections as the theoretical basis. The research method in this research is a case study and the research approach in this research is descriptive-qualitative. The conclusion of this research shows that the political communication strategy used by PSI Jakarta to gain votes is by paying attention to the figures, stabilizing the institution, and creating togetherness. They also combined their politics communication strategy with the politics communication itself, in order to gain a lot more votes. Pemilu Legislatif Tahun 2019 diikuti banyak partai politik di Indonesia salah satunya partai baru, Partai Solidaritas Indonesia (PSI). Semakin banyak partai politik mengikuti Pemilu, semakin ketat kompetisi antar partai untuk mendapatkan kursi di parlemen. PSI tidak lolos memperebutkan kursi DPR RI, tetapi berhasil mendapatkan suara 6,68% atau delapan kursi di DPRD DKI Jakarta. Penelitian ini ingin mengetahui strategi komunikasi politik PSI Jakarta atas perolehan suara di DPRD DKI Jakarta pada Pemilu 2019. Landasan teoritik yang digunakan adalah konseptualisasi komunikasi politik, konseptualisasi strategi komunikasi politik, konseptualisasi partai politik, dan konseptualisasi pemilihan umum. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan strategi komunikasi politik PSI Jakarta untuk memperoleh suara yakni dengan merawat ketokohan, memantapkan kelembagaan, dan menciptakan kebersamaan. PSI Jakarta juga mengkombinasikan strategi komunikasi politik dengan unsur komunikasi politik.